The time-course of broiler intestinal microbiota development after administration of cecal contents to incubating eggs - Erin E. Donaldson; Dragana Stanley; Robert J. Hughes; Robert J. Moore (PeerJ, 2017)
Background The microbial populations that inhabit the gastrointestinal tract (GIT) are known to influence the health and growth performance of the host. Clean hatcheries and machine-based incubation practices in the commercial poultry industry can lead to the acquisition of aberrant microbiota in the GIT of chickens and a very high level of bird-to-bird variation. The lack of microbial profile flock uniformity presents challenges for harnessing and manipulating intestinal bacteria to better serve the host. Methods Cecal contents from high or low performing chickens were used to inoculate the surface of eggs prior to hatching and then the initial gut colonisation was monitored and subsequent changes in gut microbiota composition were followed over time. Two different cecal treatment groups were compared to an untreated control group (n = 32). Bacterial communities were characterised using high-throughput 16S rRNA gene sequencing techniques. Results Cecal microbiota transfer via egg surface application did not transfer the performance profile of the donors to the recipient birds. One of the cecal inoculations provided a more uniform gut microbiota, but this was not reproduced in the second group with a different inoculum. Development of the intestinal community was reproducible in all three groups with some genera like Lactobacillus showing no change, others like Faecalibacterium increased in abundance slowly and steadily over time and others like Enterobacter were abundant only in the first days of life. Discussion The cecal treatment reduced bird-to-bird variation in microbiota composition. Although the high FCR performance of donor birds was not transferred with the cecal microbiota, all three groups, including the control, performed better than standard for the breed. The pattern of microbiota development was similar in all three flocks, indicating that the normal processes of microbiota acquisition largely swamped any effect of the cecal material applied to eggs.